1987
DOI: 10.7863/jum.1987.6.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Fetal bowel. Normal sonographic findings.

Abstract: The normal sonographic appearance of fetal colon and small bowel is reported in a prospective study of 130 fetuses. The colon, which appeared as a continuous tubular structure located around the perimeter of the abdominal cavity, was seen in some fetuses as early as 22 menstrual weeks and in all fetuses examined after 28 weeks. Colon diameter demonstrated a linear relation (r = 0.82) with menstrual age, reaching a maximum of 18 mm at term. In comparison, small bowel was located centrally and individual segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 7 publications
4
38
1
3
Order By: Relevance
“…Fetal smallbowel peristalsis is normal and is usually present, while colon peristalsis is not generally observed. 7 However, in our cases the focally dilated loops of bowel that contained the calcified meconium were active and were later shown to be the colon.…”
Section: Discussionmentioning
confidence: 45%
“…Fetal smallbowel peristalsis is normal and is usually present, while colon peristalsis is not generally observed. 7 However, in our cases the focally dilated loops of bowel that contained the calcified meconium were active and were later shown to be the colon.…”
Section: Discussionmentioning
confidence: 45%
“…These results were similar to the findings of Zalel et al and Nyberg et al who found that colon diameter demonstrated a linear relationship with menstrual age, reaching a maximum of 18 mm at term. 12,13 In this study, we found that for fetuses with colon diameter equal to or greater than 12mm, 58.7% were 37 weeks or older, with a sensitivity of 81.8% and specificity of 71.6%. For fetuses with colon diameter equal to or greater than 14 mm, 64.7% were 37 weeks or older with a sensitivity of 33.3% and specificity of 91.0%.…”
Section: Discussionmentioning
confidence: 79%
“…10 Although many studies have been done among western population to determine the relationship between various features of the intestinal development and the gestational age, there is paucity of data from Indian population. 3,5,[11][12][13] In this study, we have studied the relationship of maximum diameter of the fetal descending colon with the gestational age between 32 to 40 weeks of gestation and tried to verify whether fetal colon diameter can be used for estimating the gestational age of fetuses among Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…İnce ve kalın barsakların genişlikleri gebelik haftası ile birlikte artış gös-termekte olup gebelik haftasına göre nomogramlar bulunmaktadır [4,5]. Üçüncü trimesterde ince barsak çapları 7 mm'yi, uzunlukları 15 mm'yi; inen kolon çapı 18 mm'yi, rektum çapı…”
Section: Gastrointestinal Sistemin Normal Ultrason Görünümüunclassified